Correlation between Histological Depth Invasion & Metasis of Anterior 2/3rd of Tongne & Buccal Mucosa - Mouneshkumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: When compared to other imaging modalities, such as CT or MRI, ultrasonography(US) offers the highest spatial resolution for soft tissues, allowing it to reveal structural detail down to the millimeter scale. Aim: To determine and evaluate the correlation between H-DOI & CLNS of OSCC of anterior 2/3rd of tongue & BM. Material & method: 33 patients were included for the tretament of OSCC then the probe was then placed directly on the lesion & DOI was measured in a vertical plane from the adjacent normal surface epithelium to the point of maximal depth and checked for HE. Result: We found that , intraclass correlation was 0.981 which was highly significant depicting HE and US-DOI showed strong correlation. Conclusion: There was a strong correlation between DOI and the occurrence of metastasis.